Peran Kontrol Diri terhadap Celebrity Worship Pada Kpopers di Indonesia: Penelitian - Habibiyu Furqon; Hasnida; Rahma Fauzia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The K-Pop phenomenon has become a part of global popular culture, including in Indonesia, with a significant impact on the behavior and lifestyle of its fans. One form of attachment to idols that arises is celebrity worship, a parasocial relationship which, if excessive, can have negative psychological effects. This study aims to examine the influence of self-control on celebrity worship among K-Pop fans. The research used a quantitative method with a correlational approach. Participants consisted of 400 K-Pop fans aged 18 and above, selected using purposive sampling. The instruments used were a self-control scale based on De Ridder’s theory (2004) and the Celebrity Attitude Scale (CAS) by Maltby (2006). Data analysis was conducted using simple linear regression. The study aimed to determine the effect of celebrity worship on self-control. The analysis showed that celebrity worship has a positive and significant influence on self-control, with a coefficient of determination (R²) of 0.080. This means that 8% of the variation in self-control can be explained by celebrity worship, while the remaining 92% is influenced by other factors. These findings suggest that the higher the level of admiration for celebrities, the higher a person's self-control tends to be, although the contribution is relatively small